Highly Efficient Water-Based Extraction of Biliprotein R-Phycoerythrin From Marine the Red-Macroalga Sarcopeltis skottsbergii by Ultrasound and High-Pressure Homogenization Methods - Castro-Varela, Pablo; Celis-Pla, Paula S.M.; Figueroa, Felix L.; Rubilar, Monica (Frontiers in Marine Science, 2022)
Sarcopeltis skottsbergii is an endemic species of the southern region of South America, with R-phycoerythrin (R-PE) as an accessory photosynthetic pigment. The production of S. skottsbergii is around twenty thousand tons of dry alga per year. The evaluation of (R-PE) in a biorefinery model is still incipient in the algal biotechnology area and will be used in the food, pharmaceutical, cosmeceutical, and nutraceutical industries. This work evaluated the cell disruption and separation processes by using two green technologies, ultrasound-assisted extraction (UAE) and high-pressure homogenization (HPH), to obtain an R-phycoerythrin enriched extract from S. skottsbergii. Two-levels three-factor central composite design (CCD) and response surface methodology (RSM) were carried out to optimize the extraction conditions, including the factors for UAE (time, amplitude, and solvent) and HPH (Pressure, number of passes, and solvent). Additionally, a second-order polynomial fit was performed to fit the experimental data by the green method. HPH method was the most efficient extraction method under the conditions obtained of 100-400 MPa pressure power, 2-3 number of passes, and distilled water as solvent. Furthermore, the experimental extraction yields ranged from 4.4-5.7 mg of PE g-1 of dry biomass under the optimal extraction conditions (400 MPa; 2 passes), which agreed with the predictive yield of 4.6-5.5 mg g-1 DW. The ultrafiltration membrane used for the separation process for both methods exhibited a rejection of R-phycoerythrin concentrated at 30 KDa. Furthermore, R-phycoerythrin showed a positive correlation between the antioxidant capacity (ORAC) in the best-selected extractions. After the extraction, the same pattern was observed in Chlorophyll a and total carotenoids with DPPH. Thus, it was an attractive non-aggressive extraction alternative with biological activity of interest for formulating biotechnological products for the food industry is suggested.